PENGARUH KOMITMEN ORGANISASI, SELF EFFICACY, DAN ORGANIZATIONAL CITIZENSHIPBEHAVIOR (OCB) TERHADAP KINERJA KARYAWAN (Studi Kasus Pada Karyawan Tetap Susan Spa & Resort Bandungan) - Hikmah, Nurul; Nugraha, Hari Susanta (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2018)
Susan Spa & Resort Bandungan is a service company offering lodging services such as resorts and SPA. The problems in this research is the fact that employee turnoverÂ¸ increased employee absenteeism, low awareness to help each other and low achievement. This indicates low employee performance. Susan Spa & Resort Bandungan need to take attention to factors affecting employee performance to increase work productivity so that can compete with other service companies. The purpose of this study is to identify the influence of commitment organizational, self efficacy, and organizational citizenship behavior (ocb) for employee performance (case study on permanent employees Susan Spa & Bandungan Resort) in Semarang Regency. The type of this research using explanatory research. The sample used are 38 respondents respondents permanent employee Susan Spa & Resort Bandungan. The sampling techniques is Saturation Sampling method. The data collection technique are questionnaire and literature review. Data analysis techniques are using validity test, reliability test, cross tabulation test, correlation test, determination test, simple linear regression, multiple linear regression, t test, and f test with SPSS 21.0. The conclusion of this study is that there is a positive and significant between, organizational commitment, self efficacy, and organizational citizenship behavior (ocb) influece to the employee performance partially and simultaneously. The recommendation for the company to improve self efficacy of employees from indicators solutional (able to give the best advice), leadership (teamwork) and experience ( experience from failure). In addition, the company also have to improve organizational citizenship behavior (ocb) employees from indicators volunteer to help (help other employees without rewards), competition (to be the best employee), avoid conflict, participation (participation in the activities company), initiative (looking for information of competitors and new trend), and fairness (not spending time to raise the issue).